Monitoring of high-intensity focused ultrasound treatment by shear wave elastography induced by two-dimensional-array therapeutic transducer. (13th June 2016) - Iwasaki, Ryosuke; Takagi, Ryo; Nagaoka, Ryo; Jimbo, Hayato; Yoshizawa, Shin; Saijo, Yoshifumi; Umemura, Shin-ichiro
Abstract: Shear wave elastography (SWE) is expected to be a noninvasive monitoring method of high-intensity focused ultrasound (HIFU) treatment. However, conventional SWE techniques encounter difficulty in inducing shear waves with adequate displacements in deep tissue. To observe tissue coagulation at the HIFU focal depth via SWE, in this study, we propose using a two-dimensional-array therapeutic transducer for not only HIFU exposure but also creating shear sources. The results show that the reconstructed shear wave velocity maps detected the coagulated regions as the area of increased propagation velocity even in deep tissue. This suggests that "HIFU-push" shear elastography is a promising solution for the purpose of coagulation monitoring in deep tissue, because push beams irradiated by the HIFU transducer can naturally reach as deep as the tissue to be coagulated by the same transducer.